Antiretroviral Drug Use and HIV Drug Resistance Among HIV-Infected Black Men Who Have Sex With Men: HIV Prevention Trials Network 061. (1st August 2015) - Chen, Iris; Connor, Matthew B.; Clarke, William; Marzinke, Mark A.; Cummings, Vanessa; Breaud, Autumn; Fogel, Jessica M.; Laeyendecker, Oliver; Fields, Sheldon D.; Donnell, Deborah; Griffith, Sam; Scott, Hyman M.; et al.
Abstract : Background: HIV Prevention Trials Network (HPTN) 061 enrolled black men who have sex with men in the United States. Some men with low/undetectable HIV RNA had unusual patterns of antiretroviral (ARV) drug use or had drugs detected in the absence of viral suppression. This report includes a comprehensive analysis of ARV drug use and drug resistance among men in HPTN 061 who were not virally suppressed. Methods: The analysis included 169 men who had viral loads >400 copies per milliliter at enrollment, including 3 with acute infection and 13 with recent infection. By self-report, 88 were previously diagnosed, including 31 in care; 137 men reported no ARV drug use. Samples from these 169 men and 23 seroconverters were analyzed with HIV genotyping and ARV drug assays. Results: Forty-eight (28%) of the 169 men had ≥1 drug resistance mutation (DRM); 19 (11%) had multiclass resistance. Sixty men (36%) had ≥1 ARV drug detected, 42 (70%) of whom reported no ARV drug use. Nine (23%) of 39 newly infected men had ≥1 DRM; 10 had ≥1 ARV drug detected. Unusual patterns of ARV drugs were detected more frequently in newly diagnosed men than previously diagnosed men. The rate of transmitted drug resistance was 23% based on HIV genotyping and self-reported ARV drug use but was 12% after adjusting for ARV drug detection. Conclusions: Many men in HPTN 061 had drug-resistant HIV, and many were at risk of acquiring additional DRMs. ARV drug testing revealed unusual patterns of ARV drug use and provided a more accurate estimate of transmitted drug resistance. Abstract : Supplemental Digital Content is Available in the Text.